Enhancing Communication Skills of Vocational High School Students through Cooperative Learning Type Group Investigation - Ariyanto, Sudirman Rizki; Suprianto, Bambang; Umaroh, Susi Tri; Soeryanto (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2023)
Through the Cooperative Learning type Group Investigation (CL-GI), this study seeks to improve students' communication abilities. The beginning ability was taken into account as a moderator variable in this quasi-experimental investigation, which was carried out using a 2x2 factorial design. The study's participants were LVE 1 and 2 students in the 10th grade at Vocational High School (VHS) YPM 8 Sidoarjo. After performing several preliminary tests, such as normality and homogeneity tests, a two-way ANOVA was used to analyze the data. Numerous inferences can be made in light of the findings and debate. First off, kids who learnt with CL-GI had much better communication abilities than those who learned with DI. Second, students with strong initial abilities had much better communication skills than students with poor initial abilities. Thirdly, there was no discernible connection between the learning model and students' starting points in terms of communication abilities in the basics of automotive engineering.